Enhancing Interfacial Properties of Mg2Si‐Based Thermoelectric Joint with Mg2SiNi3 Compound as Electrodes. Issue 15 (8th June 2020) - Chen, Shaoping; Chen, Yanzuo; Ohno, Saneyuki; Xu, Libin; Fan, Wenhao; Xue, Lin; Ferhat, Marhoun; Wu, Yucheng
Abstract : The phase component and its evolution during aging at the joint between thermoelectric (TE) materials and electrodes are of much importance to the quality and the performance of the TE devices. While the figure of merit zT of TE materials determines the maximum efficiency of TE devices, undesired side reactions causing the growing interfacial resistance or mechanical failures between TEs and metal electrodes limit the actual performance of devices. Herein, the candidate electrode materials (Mg2 Ni and Mg2 SiNi3 ) for Mg2 Si are explored, which is one of the cost‐effective and environmentally friendly TE materials exhibiting high zT . The electrodes are directly bonded to Mg2 Si by field‐activated pressure‐Assisted sintering (FAPAS) in one‐step process. The interfaces of fabricated joints with different sintering times are monitored by electron microscopy, followed by the measurement of shear strength and the contact resistances. Outperforming strength (28.29 MPa) and contact resistance (63 μΩ cm 2 ) are observed with Mg2 SiNi3 at the joint bonded for 30 min. A long‐term stability test on Mg2 SiNi3 /Mg2 Si joint reveals a minute increase in the contact resistance as well as sufficient mechanical stability, suggesting that Mg2 SiNi3 is a great candidate of the electrode materials for Mg2 Si. Abstract : A promising candidate electrode materials, Mg2 SiNi3, for Mg2 Si thermoelectric material is proposed for the first time. The interfacial properties, strength, and contact resistance are optimized using Mg2 SiNi3 as electrodes for Mg2 Si due to the interfacial structure and the reduction of Schottky barrier height.